Visual analog scale foot and ankle (VAS-FA): Reliability and validity of the Persian version - Zarei, Hooshmand; Nosratpour, Miad; Moteshakereh, Seyed Mohammadmisagh; Mahdavi, Mahyar; Sabaghzadeh, Amir (Foot and ankle surgery, 2025)
Our purpose was to evaluate the reliability and validity of the Persian version of the visual analog scale foot and ankle (VAS-FA) among patients with foot and ankle problems and healthy subjects. The VAS-FA was translated and adapted into Persian (Farsi). Then, 82 participants, including 41 healthy subjects and 41 patients with foot and ankle problems, fulfilled the questionnaire in two sessions. The validity was assessed by correlating VAS-FA with the Persian version of the foot and ankle outcome score (FAOS) and the foot and ankle ability measure (FAAM). Intraclass correlation coefficient (ICC) and Cronbach's α were used to assess test-retest reliability and internal consistency. There was a statistically significant difference between healthy participants and patients regarding the total VAS-FA score and its subscales (P < 0.001). The test-retest reliability was excellent, and the internal consistency was good to excellent. The correlation between the total VAS-FA score and FAAM and FAOS scores was good for the healthy subjects and good to excellent for patients. The Persian version of VAS-FA is valid and reliable.